Ethnography of Communication Shifting the Meaning of the "Madduppa" Cultural Tradition in Sidrap Regency - Karmila, Andi; Bahfiarti, Tuti; Farid, Muhammad (Jurnal Komunikasi, 2024)
The development of the times has resulted in differences in perceptions regarding the application of a culture, the fading of local classical cultural values due to the integration of modern culture which brings with it new values, which has triggered a shift in thought patterns and the meaning of a tradition, including madduppa culture. In Bugis tradition, madduppa is the activity of inviting by meeting the person being invited, with the intention that the person being invited can directly attend the wedding party and give blessings to the bride and groom. This research aims to identify shifts in the meaning of the madduppa cultural tradition in Sidrap Regency, South Sulawesi Province. This research uses qualitative methods, with an ethnographic communication approach, there are two types of data processing, namely primary and secondary, data collection techniques are observation, determining informants, conducting in-depth interviews, and document processing. Miles, Huberman, and Saldana's analysis techniques, namely data condensation (selecting, simplifying, abstracting, and/or transforming), data display (presenting data), and conclusion drawing or verification (drawing conclusions). Based on the results of the research conducted, it was found that there has been no shift in the meaning of the madduppa tradition, the tradition is still practiced today but has experienced a shift, namely the procedures for implementing it, the cause is technological advances causing the desire to make the implementation of the invitation process more practical, there are procedures for implementing it clashing with religious law, as well as a lack of knowledge and in-depth understanding of madduppa cultural traditions in society.